Shared amino acid sequences between major histocompatibility complex class II glycoproteins, type XI collagen and Proteus mirabilis in rheumatoid arthritis. Issue 3 (March 1995) - Wilson, C; Ebringer, A; Ahmadi, K; Wrigglesworth, J; Tiwana, H; Fielder, M; Binder, A; Ettelaie, C; Cunningham, P; Joannou, C
Abstract : OBJECTIVES--To show molecular similarity between two sequences of Proteus mirabilis (haemolysin--ESRRAL; urease--IRRET) with HLA-DR antigens (EQRRAA) which are associated with rheumatoid arthritis (RA) and type XI collagen (LRREI), respectively; and, in patients with RA, to measure levels of antibody against a 16-mer synthetic peptide containing the ESRRAL sequence, and the haemolysin and urease proteins of Proteus mirabilis. METHODS--The homologous sequences EQRRAA and ESRRAL were modelled with Alchemy III, using the crystalline structure of DRB1*0101 (HLA-DR1). Sera from 40 patients with RA, 30 with ankylosing spondylitis (AS), and 30 controls were tested against synthetic ESRRAL peptide and the haemolysin of Proteus mirabilis by enzyme linked immunosorbent assay. Similar tests were also carried out on sera from 20 patients with RA, 40 with AS, and 15 controls, against Proteus mirabilis urease. RESULTS--Molecular modelling of the homologous sequences ESRRAL/EQRRAA and IRRET/LRREI showed stereochemical similarities. Antibodies to the 16-mer synthetic peptide containing the ESRRAL sequence, the haemolysin, and urease proteins were significantly increased in RA patients compared with AS patients (p < 0.001) and healthy controls (p < 0.001). No such increases were observed with three control peptides including the EDERAA sequence of DRB1*0402 (HLA-DR4/Dw10), the haemolysin proteins of Streptococcus pyogenes and Vibrio parahaemolyticus, and the urease of Bacillus pasteurii. CONCLUSION--The additive effect of the immune responses to the two Proteus mirabilis antigens, haemolysin (ESRRAL) and urease (IRRET), could be relevant in the aetiopathogenesis of RA.